Monkeypox virus and type 1 diabetes: a molecular insight into inflammatory signaling and β-cell autoimmunity - Yahya A. Almutawif; Haydar M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Hamza M. A. Eid; Athanasios Alexiou; Marios Papadakis; Mohammed E. Abo‑El Fetoh; Gaber El-Saber Batiha (Virology Journal)
Abstract The current worldwide pandemic of monkeypox (MPXV) elicited apprehensions over its possible long-term health ramifications. Recent data indicate a potential association between MPXV infection and the onset of autoimmune disorders, such as type 1 diabetes (T1D). This article analyzes the possible methods for MPXV infection to induce autoimmune responses and damage pancreatic β-cells. We examine from published articles the possible MPXV-induced immune dysregulation and inflammation in the development of T1D. Utilizing insights from other diabetogenic viruses, such as enterovirus and SARS-CoV-2. Currently, the association between MPXV and the development of T1D is scarce. Therefore, additional studies are essential for establishing a conclusive causal link between MPXV and T1D. Graphical abstract